Positive Politeness Strategies Used by the Characters in Elemental: Forces Of Nature Movie - Bramanta, I Kadek Gio; Indriani, Ketut Santi (Peneliti.net, 2025)
This study, titled Positive Politeness Strategies Used by the Characters in Elemental: Forces of Nature Movie, investigates the various forms of positive politeness strategies used by the characters and the underlying factors influencing their application within the movie script. The data were sourced from the official script of Elemental (2023), a film produced by Pixar Animation Studios. The research employs a qualitative method and is grounded in the politeness strategy framework developed by Brown and Levinson (1987). Findings reveal that the characters' dialogues reflect all fifteen types of positive politeness strategies. These include showing concern for the hearer, using exaggerated expressions, applying in-group markers, making promises, and encouraging shared involvement between speaker and hearer. The use of these strategies is shaped by three major factors: the intended payoff, the level of social distance, and the relative power between speakers.